An Involvement of Oxidative Stress in Endoplasmic Reticulum Stress and Its Associated Diseases - Bhandary, Bidur (MDPI, 2012)
The endoplasmic reticulum (ER) is the major site of calcium storage and protein folding. It has a unique oxidizing-folding environment due to the predominant disulfide bond formation during the process of protein folding. Alterations in the oxidative environment of the ER and also intra-ER Ca(2+) cause the production of ER stress-induced reactive oxygen species (ROS). Protein disulfide isomerases, endoplasmic reticulum oxidoreductin-1, reduced glutathione and mitochondrial electron transport chain proteins also play crucial roles in ER stress-induced production of ROS. In this article, we discuss ER stress-associated ROS and related diseases, and the current understanding of the signaling transduction involved in ER stress.